PENDAMPINGAN UMKM DALAM MENINGKATKAN DAYA SAING UMKM TOKO FOTOCOPY BENUA JAYA DENGAN METODE ILO SCORE - Lestari, Hesti; Nadila, Astri Evarista; Manggu, Blasius (Jurnal Pengabdian Bukit Pengharapan, 2023)
The aim of this community service is to increase the competitiveness of Benua Jaya shop MSMEs. By implementing the ILO Score method, the Benua Jaya Photocopy Shop needs effective assistance to increase its competitiveness in the highly competitive photocopy industry. This article discusses how MSME assistance can increase competitiveness by using the 5S module and layout. Benua Jaya Photocopy Shop is a shop that was founded in 2004. The problems with this photocopy shop are that the product layout is still not neat, rubbish is still found scattered around, lots of used paper is piled up. Therefore, MSME assistance needs to be applied to Benua Jaya photocopy shops in order to increase productivity, service quality and competitiveness.